Immersing Digital Technology in Empowering University Students with Future Skills: Digital Fabrication Laboratory Workshop - Fibonacci, Anita; Kadarohman, Asep; Hernani, Hernani; Rahmawati, Triannisa; Hana, Muhammad Nurul; Nais, Miarti Khikmatun; Razani, Ahmad Nafran; Haunan, Vito Winata; Roslan, Roslinawati Mohd (Phenomenon : Jurnal Pendidikan MIPA, 2024)
This study aimed to explore the perception of students in higher education regarding the role of digital fabrication laboratories in equipping students with the skills they need in the future. This study was conducted using a descriptive approach. The study was carried out through a DFL workshop involving students’ representation from the Department of Student Association from a state university in the West Java with a total population of 106 students. A purposive sampling technique was used to choose the participants, with total sample was 12 students. Data collection was carried out through survey and interviews to measure students' perspectives on the opportunities to use Digital Fabrication Laboratory in developing future skills in a workshop scheme. Quantitative data analysis was carried out using descriptive statistics using mean scores and percentages, while for the results of the interviews, using a thematic analysis. Study showed that according to participants, the Digital Fabrication Laboratory facility was able to develop several skills, namely creativity (14%), computational thinking (7%), soft skills (7%), teamwork (7%), technological literacy (22 %), entrepreneurship (14%) and digital design (29%). The results also showed that the digital fabrication laboratory has a role and benefits for students' future careers, with a mean score of 4.44 (very good). The results of the thematic analysis showed that participant perspective the advantages of DFL workshop can develop their skill namely entrepreneurship, souvenir entrepreneurship, business in Clothes Printing Properties, Gundam entrepreneurship, Support in entrepreneurship Courses, Teaching Media Supplier, so it can be concluded that students feel that the DFL workshop is useful for students' future careers.